ANALISIS KONSENTRASI SPASIAL INDUSTRI MINYAK KELAPA DI KOTA BITUNG - Genifer Genifer; Mex L. Sondakh; Caroline B.D. Pakasi (COCOS, 2015)
ABSTRACT This study aimed to analyze the spacial concentration of oil industry in Bitung City. Data collection lasted for 2 months from April 2015 until May 2015, ranging from the preparation phase, the data collection stage to the stage of the preparation of research reports from the month of July 2014 - February 2015. The data used are secondary data obtained from the relevant agencies Agency Statistics Center of North Sulawesi Province, Bappeda Bitung City, Disperindag Bitung City and Plantation Office Bitung. In addition, secondary data were also obtained from PT.Multi Vegetable Sulawesi, PT.Bimoli, PT.Agromakmur Jaya as three palm oil industrial company in the city of Bitung. Study of spatial concentration will be identified by descriptive quantitative. Data were analyzed using a gravity model based Hansen Gravity Model. The results showed that the closer the distance between the center of the port industry, the level of accessibility in this regard will be even greater appeal. Assuming if total employment remained. Vice versa if the total employment increase the accessibility or appeal 2 Â will be even greater. It shows that one factor is the main attraction of industrial locations in the nearby port city of Bitung is container / container as one of the factors affecting the industrial activity. Moreover, it can also be a means of transportation in the city of Bitung is wide roads, making it easier vehicle factory / company to perform the activity. The conclusion that the spatial concentration of oil industry in the city of Bitung is caused by the proximity to the port, availability of labor and the availability of raw materials, thus improving the accessibility of the attractiveness of the palm oil industry in the city of Bitung. Keywords : Spacial Concentration Analysis Of Coconut Oil Industry